The Impact of Health-Oriented Leadership on Follower Health: Development and Test of a New Instrument Measuring Health-Promoting Leadership. (February 2014) - Franke, Franziska; Felfe, Jörg; Pundt, Alexander
Based on previous research on leadership and follower health, three questions need to be answered or clarified. These questions refer to what health-specific leadership behavior is, whether motivational and cognitive aspects provide information beyond such behavior, and what role followers play in the leadership-health link. We introduce a new concept and measure of Health-oriented Leadership (HoL). This concept combines leaders' health-specific orientation towards followers (StaffCare; i.e., health behavior, health awareness, and value of health) and followers' health-specific attributes toward themselves (SelfCare). We present tests of construct and criterion validity from two field studies. The findings of Study 1 (N = 535) provide evidence for the construct validity of the HoL instrument. Study 2 (N = 383) examined the impact of StaffCare and SelfCare on follower health. As hypothesized, StaffCare as health-specific leadership is related to followers' state of health, irritation, health complaints, and work–family conflicts. These effects were shown independently from transformational leadership indicating incremental validity. Moreover, the relationship between StaffCare and these outcomes is mediated by followers' SelfCare. The findings contribute to a more comprehensive picture of ways in which leaders can promote follower health by (a) engaging in StaffCare and (b) fostering followers' SelfCare.